2011
DOI: 10.1007/s12011-011-9279-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Dietary Cadmium and Benzo(a)pyrene on Metallothionein Induction and Apoptosis in the Liver and Kidneys of Bank Voles

Abstract: Bank voles free living in a contaminated environment have been shown to be more sensitive to cadmium (Cd) toxicity than the rodents exposed to Cd under laboratory conditions. The objective of this study was to find out whether benzo(a)pyrene (BaP), a common environmental co-contaminant, increases Cd toxicity through inhibition of metallothionein (MT) synthesis-a low molecular weight protein that is considered to be primary intracellular component of the protective mechanism. For 6 weeks, the female bank voles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…; Salińska et al. ). Although epidemiological, cell culture, and animal experimental studies have shown an increased cancer incidence associated with heavy metals intoxication (Sunderman ; Trott et al.…”
Section: Metabolic Rate As a Main Cause Of Cell Conditionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Salińska et al. ). Although epidemiological, cell culture, and animal experimental studies have shown an increased cancer incidence associated with heavy metals intoxication (Sunderman ; Trott et al.…”
Section: Metabolic Rate As a Main Cause Of Cell Conditionmentioning
confidence: 98%
“…Influence of toxins, heavy metals, and other mutagenic factors on cellular DNA is considered a main cause of tumor development (Voth and Ballard 2005;Khlifi and Hamza-Chaffai 2010;Włostowski et al 2010). Chronic exposure to any of these produces damage primarily to the metabolically active tissues (e.g., liver, kidneys, and intestines), including cellular degeneration and apoptosis, DNA mutations, interstitial inflammation, and whole organ dysfunction (e.g., Maciak et al 2011b;Sali nska et al 2012). Although epidemiological, cell culture, and animal experimental studies have shown an increased cancer incidence associated with heavy metals intoxication (Sunderman 1984;Trott et al 1995;Oller et al 1997;Salnikow and Zhitkovich 2008), the mechanisms of carcinogenesis remain poorly understood.…”
Section: Toxicity Metabolism and Cancerogenesismentioning
confidence: 99%
“…As an illustration of this, MT null mice are more sensitive to Cd toxicity, including nephrotoxicity, indicating that MT-metal complexes are protective of renal function. Induction of MT by means other than metals, such as with polycyclic aromatic hydrocarbons, also protects against the effects of Cd, at least in the kidney and liver of bank voles [22]. MT, when bound with metals, especially when those metals are toxic (e.g., Cd, Hg, Pb) is more resistant to degradation in the lysosome and more likely to be excreted by the kidney in a nephrotoxic form [21].…”
Section: Mechanismsmentioning
confidence: 99%
“…For example, type I diabetics were administered 30 mg/day of Zn with no adverse effects on Cu status and an improvement in indicators of oxidative stress [39]. Nephrotoxicity would be a concern, however, the protection of induced MT on the kidney [22], and the antioxidant effects of vitamin E and Zn [23,25], as well as a slow mobilization of metals should mitigate this risk. Renal compromised patients would need additional supervision.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The consequences of exposures to lead, cadmium (Cd), and mercury and the consequent pathological changes in the liver, kidney and bone are well documented. [2][3][4][5][6][7][8][9][10] Moreover, thorium (Th), cadmium, lead, chromium (Cr), nickel (Ni), and beryllium (Be) are heavy metals with confirmed carcinogenic effects in animals and humans.11-15 Thus, there is an increasing evidence that the exposure to heavy metals could be associated with the occurrence of lung, liver, bladder, kidney, colon and skin cancer. 15 One of the most widely used heavy metals is lead.…”
Section: Introductionmentioning
confidence: 99%